Actual Production History: New Citrus Fruit Insurance Policy - Singerman, Ariel (EDIS, 2022)
The Actual Production History (APH) policy offers coverage against yield losses based on historical farm records. Given the negative impact of HLB on Florida citrus yield and the reliance of APH on the rolling average record of yield for the previous 10 seasons, the APH guarantees are higher than what they would be if the downward trend was taken into account. For growers, this means that, until such an issue is corrected, obtaining coverage under APH will likely be beneficial because the policy currently overcompensates for losses.